Assessing personality traits, life balance domains, and work addiction among entrepreneurs. Issue 3 (1st June 2022) - Therthani, Sumedha; Balkin, Richard S.; Perepiczka, Michelle; Silva, Sarah; Hunter, Quentin; Juhnke, Gerald A.
Abstract: The association between personality traits, life balance domains, and work addiction among entrepreneurs was investigated. Multiple regression and canonical correlation analysis of 106 participants indicate a significant relationship between personality traits, life balance domains, and work addiction. In particular, neuroticism was positively related to work addiction, as suggested in earlier studies. Among all the life balance domains five of the 10 life balance domains had a significant positive relationship with work addiction: positive orientation, substance use, sleep disturbance, stress/anxiety, and friendship. Results obtained from this study will help career and mental health counselors better understand entrepreneurs' needs and life balance domains. By identifying neuroticism and stress levels among entrepreneurs, career counselors can better understand work addiction tendencies and use appropriate interventions accordingly.